BAURAN PROMOSI DAYA TARIK WISATA CURUG SEWU, KENDAL - Priyanto, Muhammad Irfan; Suwena, I Ketut; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
Curug Sewu waterfall is the highest waterfall in Central Java province, Curug Sewu waterfall is a leading tourist attraction owned by Kendal Regency, besides having natural beauty and very cool air, Curug Sewu waterfall has artificial infrastructure such as a zoo, pond swimming pools, and children's playgrounds, so that the Curug Sewu waterfall has enormous tourism potential, in addition to having tourism potential, tourist attractions must have the right tourism strategy to attract tourists to visit, referring to this, researchers are interested in researching about " Promotion Mix of Curug Sewu Tourism Attraction, Kendal Regency (Case Study of Kendal Regency Disporapar Work Program)”. Data collection techniques in this study include observation, in-depth interviews, documentation, literature study and questionnaires. The technique of determining informants in this study uses purposive sampling which is a technique of determining informants and sources with certain objectives in accordance with the research theme. The results obtained in this study are Curug Sewu has enormous tourism potential and can be further developed, the promotional mix carried out by the Kendal Regency Disporapar is very good, with the mess selling indicator value getting the best results from the four promotional mix indicators that have been carried out by the Kendal Regency Disporapar.